Finite Element Analysis of the Key Component of Chain- type Lifting System - Jin Jiaqi; Liang Yuan; Wang Xianrong (Jixie chuandong)
In order to study the security and reliability of chain force transmission components of note-temperature steam flooding snubbing workover machine lifting operating system,the analysis is carried out by using the finite element software,the distribution of the chain static strength stress is accurately simulated,the result of chain the maximum equivalent stress is less than the yield limit of the material is obtained,and the contact portion of the pin and sleeve is easy to wear,when worn,the chain pitch increase,the service life will be reduced with the increasing of total length of the chain. On this basis,the computing and simulation analysis of the chain fatigue life are carried out,the results show that the structure of are fully satisfy the work requirements under the load conditions.